Transformation of Social Interaction Patterns among Adolescents in Tegal: A Comparison of Offline and Online Communication - Adzkar Baihaqi Zakaria; Diryo Suparto; Sarwo Edy (Jurnal Spektrum Komunikasi, 2026)
This research originates from the phenomenon of shifting communication patterns among adolescents, which are now increasingly mediated by mobile screens rather than direct physical encounters. The primary focus of this study is to conduct an in-depth analysis of the transformation in the frequency and characteristics of social interactions among teenagers in Tegal City as they transition from offline spaces to the online realm. Employing a descriptive qualitative approach through a comparative study, primary data were obtained from semi-structured interviews with informants aged 15–18. Social Information Processing (SIP) Theory serves as the analytical framework to observe the adaptation of social cues in the digital world. The results reveal that despite high daily social media usage—averaging more than 3 to 4 hours—the substantial intensity of conversation has not undergone a drastic change. Adolescents tend to compensate for the loss of non-verbal cues by using visual symbols, such as emojis and stickers, to minimize misunderstandings. Interestingly, the local identity in the form of the Tegal-Javanese dialect persists as a tool for building emotional closeness in both mediums. This study concludes that while social media excels in terms of coordination, organic intimacy and conflict resolution still rely on the richness of face-to-face interaction. The resulting transformation has birthed a hybrid interaction pattern, where the digital universe functions as a medium for relationship maintenance, while physical meetings remain the primary anchor for building emotional depth and mutual trust.